2011
DOI: 10.1186/1476-511x-10-246
|View full text |Cite
|
Sign up to set email alerts
|

Activation of peroxisome proliferator activated receptor alpha ameliorates ethanol induced steatohepatitis in mice

Abstract: BackgroundPeroxisome proliferator activated receptor alpha (PPARα) regulates lipids metabolism and inhibits inflammatory response. However, the role of PPARα in alcoholic liver disease is largely unknown. We aim to elucidate the effect and the molecular basis of PPARα in ethanol induced hepatic injury in mice.ResultsC57BL/6J mice fed with 4% ethanol-containing Lieber-DeCarli liquid diet for 12 weeks exhibited hepatocyte steatosis, necrosis and inflammatory infiltration, accompanied with elevated serum alanine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 36 publications
3
36
0
Order By: Relevance
“…By contrast, administration of synthetic PPAR␣ agonists to rodents decreases fatty liver (45)(46)(47)(48)(49)(50). This apparent discrepancy can be reconciled by the notion that Hilpda is one of more than 100 genes involved in lipid metabolism that are induced by PPAR␣.…”
Section: Discussionmentioning
confidence: 72%
“…By contrast, administration of synthetic PPAR␣ agonists to rodents decreases fatty liver (45)(46)(47)(48)(49)(50). This apparent discrepancy can be reconciled by the notion that Hilpda is one of more than 100 genes involved in lipid metabolism that are induced by PPAR␣.…”
Section: Discussionmentioning
confidence: 72%
“…Eight-week-old male C57BL/6J mice were bred and housed as previously described [5]. The mice were randomly divided into 4 groups (6 mice per group): control group, mice fed with non-alcoholic control liquid diet (TROPHIC Animal Feed High-tech Co., Ltd., Nantong, China); ethanol group, mice fed with 4% ethanol-containing Lieber-DeCarli liquid diet (TROPHIC); ethanol plus CCl 4 (ethanol+CCl 4 ) group, mice fed with ethanol liquid diet, and received 5% CCl 4 (Sinopharm Chemical Reagent Co., Ltd, Shanghai, China) dissolved in olive oil (Sinopharm) intraperitoneal injection, 2 ml/kg body weight, twice a week; ethanol plus CCl 4 and WY14643 (ethanol+CCl 4 +WY) group, mice fed with ethanol liquid diet with WY14643 (50 mg/kg/d, Cayman Chemical, Ann Arbor, MI, CA), and administrated with 5% CCl 4 intraperitoneal injection (Figure 7).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we demonstrated the role of nuclear transcription factor peroxisome proliferators activated receptor alpha (PPARα) in lipid homeostasis and modulation of inflammatory responses in alcoholic steatohepatitis [5]. Induction of PPARα significantly ameliorated the severity of ethanol induced liver injury by regulating expression of lipid metabolism and inflammation related genes.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that lipid metabolism in hepatocytes of S. hasta was modulated by Fe through the PPARα signaling pathway. Similarly, Kong et al (2011) found that the mRNA level and protein expression of FAS were enhanced by treatment of GW6471 in mice.…”
Section: Parametersmentioning
confidence: 93%